Political Ethics and European Constitution - Ferreira da Cunha, Paulo (Springer, 2016)
Is the dream of EU endangered? This book reviews classic and modern values and virtues, and uses them in order to rethink Europe’s present politics and its future. The idea of the Republic was born with the political ethics of ancient Greece. The current international crisis obliges Europe to face the mirror of truth: What has become of the European Idea and how fares the European Constitution? It has been a long road from the Greek Politeia to the present lack of values and financial monomania in Europe, who seems to have lost any harmony between the spirit, the soul and the body of her Constitution: the will and values of the people (material constitution), the text of the Lisbon Treaty (formal constitution) and its current political interpretation and action (real constitution), making Europe a two-tier or three-tier club, far from the dream of the founding fathers. Without republican values and virtues, and failing to uphold the European social model, the European Union would devolve into moral, social and democratic bankruptcy.